The art of brand war: an approach to conceptualising flanker brands - Lim, Aaron (2015)
This research seeks to develop a unified concept of flanker brands, and build a research model to empirically evaluate consumer perceptions and attitudes towards flanker brands; specifically in the luxury brand context. Underpinned by Schema Theory, applying the military teachings of Manoeuvre Theory, and incorporating the lessons from Sun Tzu’s Art of War; this research aims to dimensionalise flanker brands into Distinct and Latent Flanker Brands. In doing so, this study clarifies how flanker brands are employed in the marketplace, and how consumers react to them.